PENGARUH VARIASI PENYUDUTAN ARAH SINAR PADA PEMERIKSAAN VERTEBRA LUMBOSACRAL JOINT PROYEKSI LATERAL TERHADAP KRITERIA ANATOMI RADIOGRAF - utami, asih puji (Jurnal Ilmu dan Teknologi Kesehatan, 2011)
There are variations in x-ray beam angulation applied in examining lumbosacral joint lateral projection, both theoretical and practical. According to Clark (1973) examination of lumbosacral joint lateral projection uses beam direction of 0 °, Ballinger (1999) stated that x-ray beam is directed 5 º to 8 º caudally and Bontrager (2001) ranging from 5 º to 10 º to the caudally. The purpose of this study is to investigate the influence of x-ray beam angulation to radiographic anatomical criteria and to find the most appropriate x-ray beam angulation to achieve good radiographic anatomical criteria conducted in examining lumbosacral joint lateral projections using x-ray beam angulation of 0 º, 5 º, 10 º and 15 º caudally. The study was experimental with observational method approach.  Observation is done by examining lumbosacral joint lateral projections with the variations of x-ray beam angulations of 0 º, 5 º, 10 º and 15 º caudally. The data is collected by conducting tests, and spreading questionnaires (check list). There are 15 observers in spreading questionnaires.  Radiographic results are recorded as experimental documents.  Methods of data analysis used descriptive analysis by simple regression and crosstab data. Data are codified and categorized then. The results of this research showed that there are positive significant and correlation between x-ray beam angulation variations of 0º, 5º, 10º, 15º caudally to the radiographic anatomical criteria produced on examining lumbosacral joint lateral projection.  It is indicated by p value = 0.016 (<0.05), means Ha is accepted and Ho is rejected. The best x-ray beam angulation is 15º caudally.  This angulation can produce good radiographic anatomical criteria.   Key words:  lumbosacral joint, lateral projection, x-ray beam angulation of  0 º, 5 º, 10 º and 15 º, radiographic anatomical criteria